Anti-Listeria monocytogenes effect of bacteriocin-incorporated agar edible coatings applied on cheese. (October 2019) - Guitián, M. Virginia; Ibarguren, Carolina; Soria, M. Cecilia; Hovanyecz, Paula; Banchio, Claudia; Audisio, M. Carina
Abstract: Bacteriocins synthesised by lactic acid bacteria are natural alternatives to control Listeria monocytogenes, a foodborne pathogen. Additionally, antimicrobial biopolymer coatings have significant benefits in food packaging and preservation. The effect of anti- L. monocytogenes enterocins synthesised by Enterococcus avium DSMZ17511 was evaluated when supported on agar edible films and applied as antimicrobial coatings on different cheese matrices artificially contaminated with L. monocytogenes 01/155. A decrease of at least 1 log unit in viability of the pathogen was detected. The wetter matrix of soft cheese facilitated rapid diffusion of the antimicrobials, while the drier matrix of semi hard cheese produced a gradual release with prolonged inhibition of the pathogen. Also, DSMZ17511 antimicrobial peptides, only at very high concentrations, exhibited mild cytotoxicity against L929 and Caco-2 cell lines. Therefore, application of these enterocin agar coatings could be an effective, low cost, natural and safe alternative to control L. monocytogenes in cheeses.